Synthesis of Benzoxaphosphole 1-Oxide Heterocycles via a Three-Component Coupling Reaction Involving Arynes, Phosphites, and Ketones - Jeong, Hee Jin; Kim, Ji Ho; Lee, Jae Kyun; Yoon, Hyo Jae; Choi, Junwon; Han, Seo Jung (Organic Letters, 2022)
An efficient and transition-metal-free three-component reaction with benzynes formed in situ from 2-(trimethylsilyl)aryl triflate, phosphites, and ketones was developed for the synthesis of benzoxaphosphole 1-oxides. An array of benzoxaphosphole 1-oxides were prepared from both activated and non-Activated ketones in moderate to good yields with a broad functional group tolerance. This reaction is useful for preparing organophosphorus compounds encountered in natural products and materials.